Co-pyrolysis of Empty Fruit Bunches with Palm Kernel Shell, Palm Leaves and Sawdust to Produce Fine Chemicals - Zaman, N.A.B.B.N. (Springer Science and Business Media Deutschland GmbH, 2021)
Agriculture materials of oil palm tree and forestry such as rubber tree are commonly utilised and this can be contributed to the wastes. Therefore, this research is looking for value-added to these types of materials from the production of pyrolysis oil. This paper was intended to determine the best ratio of feedstock to produce high quantity of bio-oil yield and to determine properties of chemicals produced in bio-oil. The samples of empty fruit bunches (EFB) with palm kernel shell (PKS), palm leaves (PL) and sawdust (SDT) were co-pyrolyzed with different ratios (25:75, 50:50 and 75:25) to produce liquid oil, and the yield was analyzed and characterized by using GC-MS. The results show the mixture of EFB:PKS with ratio of 25:75 produced the highest yield of 40.53, meanwhile, the co-pyrolysis of EFB:SDT produced the lowest yield which was 19.25. The chemicals for each bio-oil were determined and the major organic chemicals such as phenols, aldehydes group, methyl alcohol and acetic acids were found for the purpose products of our fine chemicals. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.